(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Childhood is a period of changes in the individual’s life, which can influence adult life. Acute Lymphoblastic Leukemia (ALL) has a high incidence among children and adolescents, with nonspecific symptoms in most cases. Objectives: To analyze the risk factors that can be identified in the face of the diagnosis of acute lymphoblastic leukemia in childhood. Methods: This is a scope review carried out from January to March 2022, using the Virtual Health Library database and using previously validated descriptors in the Health Sciences Descriptors. Results: After the search, 9 articles were selected for the respective study. Sociocultural and genetic characteristics were identified as risk factors for the diagnosis of Acute Lymphoblastic Leukemia in childhood. Conclusion: A trained team capable of identifying risk factors for Acute Lymphoblastic Leukemia is extremely important for adequate and quality care.